2018
DOI: 10.5812/aapm.67132
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preoperative Zintoma Capsule on Postoperative Nausea and Vomiting After Laparoscopic Cholecystectomy

Abstract: BackgroundPostoperative nausea and vomiting (PONV), as one of the complications after laparoscopic cholecystectomy, occurs in over 40% - 77% of cases. Considering the numerous complications of synthetic drugs, there is a growing tendency towards the use of herbal medicines due to their unique features. Ginger root is one of the herbal compounds effective on nausea and vomiting.ObjectivesThe aim of this study was to evaluate the effect of preoperative Zintoma capsules on PONV after laparoscopic cholecystectomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(36 citation statements)
references
References 25 publications
(39 reference statements)
1
9
0
3
Order By: Relevance
“…Ginger is safe and well tolerated, which appears to be useful in both pregnancy 283 285 and chemotherapy-induced PONV 286 , reducing the need for antiemetic rescue medications 287 297 . Ginger has also reduced PONV in patients undergoing cholecystectomy 287 289 , nephrectomy 282 , 291 , gynecologic/obstetric surgery 293 – 295 , ambulatory surgery 292 , cataract surgery 298 , and thyroidectomy 299 . However, there are also several studies that have reported contradictory results 300 302 .…”
Section: Perioperative Antiemetic Drugs Used For the Treatment And/ormentioning
confidence: 99%
“…Ginger is safe and well tolerated, which appears to be useful in both pregnancy 283 285 and chemotherapy-induced PONV 286 , reducing the need for antiemetic rescue medications 287 297 . Ginger has also reduced PONV in patients undergoing cholecystectomy 287 289 , nephrectomy 282 , 291 , gynecologic/obstetric surgery 293 – 295 , ambulatory surgery 292 , cataract surgery 298 , and thyroidectomy 299 . However, there are also several studies that have reported contradictory results 300 302 .…”
Section: Perioperative Antiemetic Drugs Used For the Treatment And/ormentioning
confidence: 99%
“…Also, ginger significantly reduced the severity of nausea immediately and 2 hours after recovery in patients undergoing eye surgery (P < 0.005). Seidi et al in 2017 (18) and Albooghobeish et al (20) in 2018 demonstrated that the incidence and severity of PONV were significantly lower in the ginger group than in the placebo group. These studies are similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate nausea, we used a 10 cm linear analog scale that ranged from 0 to 10; scores 0, 1 - 3, 4 - 6, 7 - 9, and 10 were assigned to no, mild, moderate, severe, and very severe nausea, respectively. Vomiting was defined as a severe gastrointestinal stimulation, which caused the forceful discharge of the contents of the digestive tract from the mouth (20). The number of vomiting episodes was recorded (21).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yapılan bir çalışmada bülantı-küsmayı o nlemek için ameliyat sonrası tek doz 4 mg Ondansetron HCl verilmiş ve bülantı-küsma yo netiminde etkili oldüg ü bildirilmiştir (10). Literatü rde bülantı küsmanın non-farmakolojik yo netimiyle ilgili birçok çalışma bülünmaktadır (19,34,35). Yapılan bir çalışmada laparoskopik kolesistektomi geçiren bireylere her iki ayag a beşer dakika ayak masajı yapılmış ve bü masajın cerrahi sonrası bülantı küsma ü zerine etkili oldüg ü rapor edilmiştir (19).…”
Section: Günübi̇rli̇k Laparoskopi̇k Kolesi̇stektomi̇ Ve Bakim Ameliyat öNcesi Hasta Hazırlığıunclassified